EFFECT OF LEAD ACETATE ON HISTOOGICAL FEATURES OF LIVER, SKELETAL MUSCLE AND TESTIS AND SERUM TESTOSTERON LEVEL OF LABORATORY ALBINO MICE Mus musculus. (Baghdad Science Journal, 2025)
Lead acetate as one of the environmental pollutants can threats the life of living creatures in many ways, it has a long half-life, accumulates mainly in the soft tissue and leads to adverse effects in these tissues. An experiment was conducted to study the effect of oral feeding of lead acetate on histological features of liver, kidney, testis and muscle of albino mice. Mice were treated with 0.05 mg/100 ml lead acetate (LA) for 10 days (group A) and for and for 20 days (group B) and for 30 days (group C).The histological section of liver of mice group A characterized by slightly blurred trabecular structure with foci of hepatitis which increased with cytoplasmic vacules in group B but in group C liver reveal necrosis, heamorrhage, hepatitis with dysplasia. Testis revealed foci of spermatic hypoplasia in group A, areas of fibrosis and spermatic arrest revealed in group B and C with mild degree of maturation in last group. Skeletal muscle fibers not changed in group A but characterized with focal mononuclear cell infiltration and myositis in group B but necrosis and skeletal muscle atrophy with increase perimuscular adipose tissue and fibrosis revealed in fibers of group C.